Internalization of Wasathiyah Islamic Value Education - Eka Yanuarti; Fadila Fadila (STAI Hubbulwathan Duri, 2022)
Digital literacy is closely related to the spread of Wasatiyah Islamic values, in modern times as it is today, information obtained from internet networks, this is possible with digital literacy to help create the internalization of Wasatiyah Islam in each individual member of the Aisiyyah recitation congregation in Rejang Lebong Regency and become part of the individual. Because in creating wasatiyah Islam, it is hoped that it must start from within the individual itself. The purpose of this study was to determine the internalization of Wasathiyah Islamic values through digital literacy in the Aisiyyah Rejang Lebong congregation. This type of research is qualitative research, using analytical techniques. The data analysis technique used uses the analytical steps carried out in qualitative research according to Miles and Huberman, namely the data collection stage, the data reduction stage, the presentation stage, and the conclusion drawing stage. The results of this study are: First, the use of Digital Literacy in the Aisiyah Recitation Congregation in Rejang Lebong Regency which is used for recitation in Rejang Lebong Regency mostly uses WhatsApp groups which are used to share tausiyah-tausiyah, remind each other to pray tahajjud or other sunnah prayers. Second, by instilling peace-loving values, implementing tolerance, and not being too concerned with fiqh laws that are khilafiyah.